Teacher and Student Ethic Concept : A Study Toward the Thought of K.H. Hasyim Asy’ari - Ikhwan Aziz Q; Niarotul Anzumi (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2019)
Ethics is a rule or moral that is present in every proposition or at every institution. Ethics is also a very important thing for community life, because without an ethic or moral human being will do everything without being treated with a sense of responsibility and good morality. In an education it is very important to have ethics or morals, in which a teacher or student in the teaching and learning process must be based on good ethics and morals. The research and data sources used in this article are obtained through library research data collection methods (literature) taken from the author's collection of books and books contained in the library. From the results of this study it can be concluded that the ethics of teachers and students are very much needed, because in a learning process both the teacher and the student must use good ethics when a learning activity takes place or when communicating between teachers, staff, and students, because it will affect the blessing of the knowledge obtained.